(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Ovarian hyperstimulation syndrome (OHSS) is an iatrogenic complication caused by excessive response to controlled ovarian stimulation. It is characterized by ovarian enlargement and the formation of multiple cysts. When OHSS occurs in spontaneous pregnancies it is known as spontaneous OHSS (sOHSS). Case presentation: A 31-year-old para 2+0 gravida 3 presented with gross abdominal distention at 11 weeks of gestation. Abdominopelvic ultrasound revealed a single viable fetus at 12 weeks and 4 days with large multicystic adnexal masses, which were suggestive of mucinous cystadenoma. Follow-up magnetic resonance imaging revealed ovarian hyperstimulation syndrome. Initial CA-125 levels were >600 U/ml. Her symptoms were mild and resolved with conservative management. She eventually delivered preterm at 33 weeks. Conclusion: Pregnancy with sOHSS is a rare condition and may not be obvious. It may mimic other ovarian tumors, leading to premature termination of a normal pregnancy and unnecessary surgical intervention.